Encouraging students' learning outcomes using the information search method - Mbaubedari, Stince; Sirait, Silvia Hanna Kusuma; Jeni, Jeni (Inornatus: Biology Education Journal, 2022)
This study aims to determine the effect of the Information Search learning method on the learning outcomes of class VIII students in science subjects at SMP Negeri 9 Sorong City. The method used in this study was a quasi-experimental design with a non-equivalent control group design. Samples were Class VIII A1 (15 students) as the experimental group and class VIII D2 (15 students) as the control group. Before treatment, both classes were given a pre-test to see if there was a difference in learning outcomes between the experimental and control group. Both classes were given a post-test to see the effect of learning on learning outcomes. Data analysis in this study used statistical analysis consisting of three stages, namely normality test, homogeneity test, and hypothesis testing using a T-test. The calculation of gain from learning outcomes is also carried out. The results of this study indicate the effect of information search methods on improving student learning outcomes (sig. = 0.001 < 0.05). The experimental class gain is 37.33, and the control class is 17.33. This research concludes that the information research method can encourage student learning outcomes.